Fillers Used by Speakers on DIVE Studios Podcast - Setyowati, Untari; Setyawan, Agustinus Hary (Linguistics and ELT Journal, 2023)
Fillers are words or sentences used in speech in order to connect concepts or link ideas during pauses in speech. This research examined the types and functions of fillers used by speakers on DIVE Studio podcast. This study aims to determine the types and functions of fillers used by speakers in the Dive Studios podcast. Furthermore, conversation analysis is used in this study to gather data. This research also uses a qualitative approach to describe the data. The study's findings revealed 479 fillers, divided into lexicalized and unlexicalized filled pauses. On the other hand, the researchers concluded that fillers have several functions related to the speaker's state. Five functions represent this research: hesitating, empathizing, mitigating, time-creating devices, and editing terms. Additionally, knowing the many kinds and purposes of fillers may assist speakers in being mindful of their speaking abilities.